The “Confidence” Trap: When the Likelihood Is Low, Forecasters Look Less Competent When They Refer to Their Confidence in an Outcome Rather Than Its Probability - Palmeira, Mauricio; Chen, Haipeng (Allan) (Journal of Consumer Research, 2026)
Abstract Marketers make various forecasts, including those about new products, financial instruments, sporting events, and medical procedures, to influence consumer decisions. In communicating the likelihood that a forecaster assigns to an outcome, the forecaster can refer to their confidence in the outcome (e.g., “I’m 30% confident”) or the probability of the outcome (e.g., “There is a 30% probability”). The authors propose that the choice of language (e.g., probability vs. confidence) affects the perceptions of forecasters, yielding predictable consequences on consumer decisions. Specifically, some languages (e.g., confident/sure/certain) encourage internal attributions (e.g., to a forecaster), whereas other languages (e.g., probability/likelihood/chance) encourage external attributions (e.g., to an outcome). As a result, expressions of a forecaster’s confidence (vs. outcome probability) make the forecaster look less competent, especially when the likelihood of the outcome is low. A series of studies shows the effect in various consumption scenarios. The effect is mediated by internal (vs. external) attributions, influences real betting decisions, and is mitigated when the likelihood is high and among consumers with a weaker tendency to make internal attributions (i.e., a weaker correspondence bias).